The Effects of Built Environment Landscaping on Site Security: Reviews on Selected Shopping Centers in Istanbul - Gökçen Firdevs Yücel Caymaz (Journal of Contemporary Urban Affairs, 2019)
In recent years, the global increase in security concerns made it inevitable to develop new action plans in planning processes. Security concerns come with the necessity of considering building architecture processes together with environmental and landscape design processes. This study aims identification of which measures can be taken into account safely built environment design. It was made a safety checklist which can be adapted for every open space. Five shopping malls around Istanbul were evaluated and some result has been achieved for their site security.